2004
DOI: 10.1128/cmr.17.4.697-728.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniaeand Its Role as a Human Pathogen

Abstract: Mycoplasma pneumoniae is a unique bacterium that does not always receive the attention it merits considering the number of illnesses it causes and the degree of morbidity associated with it in both children and adults. Serious infections requiring hospitalization, while rare, occur in both adults and children and may involve multiple organ systems. The severity of disease appears to be related to the degree to which the host immune response reacts to the infection. Extrapulmonary complications involving all of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
1,289
8
91

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,155 publications
(1,410 citation statements)
references
References 437 publications
(438 reference statements)
22
1,289
8
91
Order By: Relevance
“…Between 3 and 30 % of all cases of community-acquired pneumonia can be attributed to this micro-organism (Waites & Talkington, 2004). M. pneumoniae mainly infects older children and young adults but recent studies have shown that all age groups can be affected (von Baum et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Between 3 and 30 % of all cases of community-acquired pneumonia can be attributed to this micro-organism (Waites & Talkington, 2004). M. pneumoniae mainly infects older children and young adults but recent studies have shown that all age groups can be affected (von Baum et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These organisms lack cell walls and in nature are always associated with vertebrate hosts. Several mycoplasma species exhibit a polarized cell morphology, exemplified by Mycoplasma pneumoniae, a significant causative agent of assorted respiratory and non-respiratory human disease conditions (Waites & Talkington, 2004). This surfaceadherent organism exhibits the pleomorphy typical of its genus, but is characterized by a prosthecal terminal organelle or attachment organelle at one pole (Balish, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…M ycoplasma pneumoniae is a cell wall-less bacterial pathogen of the human respiratory tract causing primary atypical pneumonia and tracheobronchitis (1). Mycoplasmas lack major biosynthetic pathways, classical transcriptional regulators, chemotactic and other two-component systems, and the prototypical prokaryotic cell division apparatus (2,3).…”
mentioning
confidence: 99%